Bone microstructure of the pareiasaur Provelosaurus americanus from the Middle Permian of southern Brazil. (4th March 2021) - Macedo Farias, Brodsky Dantas; Schultz, Cesar Leandro; Soares, Marina Bento
ABSTRACT: Provelosaurus americanus from the Guadalupian of Brazil, is the only species of pareiasaur known from South America and its studies are limited to anatomical descriptions. Here, we examined the microstructure of limb bones, a rib fragment and osteoderms of P. americanus, aiming to answer questions related to its paleobiology. The bone tissues of this specimen comprise poorly vascularised parallel-fibred bone interrupted by growth marks indicating slow, cyclical growth. This is consistent with the pattern found in other pareisaurs from South Africa. However, the space between the LAGs are irregular and there is no clear decreasing in vascularity toward the periphery of the bone, suggesting that it did not reach skeletal maturity. The highest number of LAGs was found in the rib, suggesting that our sample lived a minimum of fifteen years. The osteoderms present a trilaminar structure consisting of a diploe composed of a cancellous core surrounded by two cortical layers. A diploe is absent from the osteoderms of previously studied South African pareiasaurs. The osteogenesis of the osteoderms is intramembraneous, but a metaplastic ossification during the early developmental stage cannot be entirely discarded, due to extensive remodeling in the central core that could have destroyed potential metaplastic tissue.